Phenology, biological and cultural control of the new almond pest Eurytoma amygdali (Hymenoptera, Eurytomidae) in Spain - Eugenia Rodrigo; Vicent Benedito; Pilar Xamaní; Manuel Baena; Francisco Ferragut (Spanish Journal of Agricultural Research)
Aim of study: Eurytoma amygdali Enderlein (Hymenoptera, Eurytomidae), the almond wasp, is a new pest detected in Spain. Although the insect is present in Europe, in Spain no damage was detected until 2016, increasing substantially in the following years. The phenology of almond wasp and the natural enemies complex were investigated and the results of the parasitism rate and cultural control measures were analyzed.